The relationship between circadian type and physical activity as predictors of sleepiness and fatigue during simulated nightshifts: a randomised controlled trial - Philip Tucker (Ergonomics, 2024)
Breaks involving physical activity may provide on-shift recovery from sleepiness and fatigue during nightshifts, with effects potentially influenced by circadian type. Thirty-three adults (M ± SD age: 24.6 ± 4.8y; 55% female) participated in five laboratory nightshifts (2200–0600h) and were randomised to sedentary (SIT; n = 14) or ‘breaking-up’ sitting (BREAK; n = 19). Participants completed the Circadian Type Inventory, categorising as rigid (n = 12) or flexible (n = 11); and languid (n = 11) or vigorous (n = 13). BREAK participants walked 3-minutes every 30-minutes at 3.2 km/h; all completed fatigue and sleepiness scales. Linear mixed models showed a 3-way interaction between nightshift (N1–N5), condition (SIT, BREAK), and rigidity-flexibility for fatigue (p<.001) and sleepiness (p<.001). Fatigue and sleepiness were greatest on N1 for SIT-Flexible and BREAK-Rigid, with SIT-Rigid experiencing the greatest levels overall. BREAK-Flexible showed no reduction. No 2-way interactions between nightshift and languidity-vigour were found. Breaking up sitting attenuated fatigue and sleepiness for rigid types only. On-shift recovery needs may differ for circadian types.